Problem Ekonomi Secular dan Respon Syed Muhammad Naquib al-Attas dalam Pandangan Islam - Amir Reza Kusuma; Mohammad Muslih (Jurnal Ilmiah Ekonomi Islam, 2023)
Economics is a fundamental principle that must be fulfilled by every individual. However, the secular economic system that promised benefits at the beginning turned out to be full of problems. Like . capitalism is the most dominant economic system in the world and even developed into a civilization that has its own worldview. Capitalism is also often claimed and accepted as a universal system that can be applied to the whole world. In responding to this way of thinking, capitalism needs to be studied and identified from its most basic concept, namely from a worldview perspective. In this case, Syed Naquib al-Attas responded that by returning to the teachings of Islam with its Shari'a and Inshaf for the sake of achieving prosperity, it is not only focused on physical things, but also metaphysical. And measuring the determination of maslahah is not limited to worldly life, but also life in the hereafter.